Evaluating the impact of CSR initiatives on the achievement of SDGs in developing economies - Tripathi, Santosh Kumar; Farooque, Asma; Ahmad, Syed Afzal (Edelweiss Applied Science and Technology, 2025)
This study explores the integration of Corporate Social Responsibility (CSR) initiatives with Sustainable Development Goals (SDGs) in developing economies, focusing on identifying best practices from leading Asian nations and their applicability to India. The research examines socio-economic and environmental outcomes, key success factors, and barriers to CSR adoption in India. A qualitative research approach is employed, including an extensive review of CSR practices in Japan, South Korea, and China. Data has been collected from corporate reports, scholarly articles, and government documents to evaluate the alignment of CSR initiatives with specific SDGs. Comparative analysis has been used to identify best practices and develop actionable recommendations for India. The study highlights that Asian countries effectively leverage socio-cultural and policy frameworks to promote impactful CSR initiatives. Notable practices include technological innovation in South Korea and community-driven models in Japan, both of which significantly contribute to achieving SDGs. In India, while CSR regulations have increased corporate engagement, challenges such as fragmented policy implementation and limited stakeholder participation persist. Policy recommendations proposed by the study include enhancing regulatory clarity, aligning CSR activities with SDG targets, and strengthening public-private partnerships to scale sustainable development efforts. This research aims to bridge the gap in understanding the integration of CSR and SDGs in developing economies by providing a comprehensive framework to improve CSR effectiveness in India.